The semiotics of evolution in contemporary church architecture - حسن فاتن; عبد الحكيم الحسيني; ميرنا نصرة (Latakia University Journal -Engineering Sciences Series, 2023)
The research focuses on semiotics and knowledge of its tools and uses in reading contemporary church architecture, where semiotic analysis constitutes an important stage in the architectural design process, and contributes to helping to guide and inform designers and architects on contemporary thought in order to produce architecture that meets the cultural and social needs of society. The architecture of religious churches, like any architecture, is subject to design principles that include a set of connotations, and the importance of realizing them helps the designer to know how to benefit from them in the production of contemporary architecture. The research reached to develop steps for architectural semiotic analysis based on two stages, the first is the description of the material product (significant) consisting of the spatial classification of how the building is positioned, access and communication systems, and the plastic classification that includes the colors used and the plastic formations in the building, and the second stage is the meanings (meaning) and is concerned with studying the perception of individuals of the building and competencies associated with the performance and understanding of human.